Construction and pure infiniteness of C^*-algebras associated with lambda-graph systems
A λ-graph system is a labeled Bratteli diagram with shift transformation. It is a generalization of finite labeled graphs and presents a subshift. In [16] the author has introduced a C^*-algebra O_L associated with a λ-graph system L by using groupoid method as a generalization of the Cuntz-Krieger algebras. In this paper, we concretely construct the C^*-algebra O_L by using both creation operators and projections on a sub Fock Hilbert space associated with L. We also introduce a new irreducible condition on L under which the C^*-algebra O_L becomes simple and purely infinite., number=1, journal=MATHEMATICA SCANDINAVICA, author=Matsumoto, Kengo, year=2005, month=Sep., pages=73–88